Foreign Financial Flows and Terrorism: A Case Study of Pakistan - Amar Anwar; Mazhar Mughal (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2016)
This study examines the differential response of various international financial flows to the post 9/11 episode of terrorism in the context of a South Asian country. Using monthly data for the period from January 2003 to December 2014, we analyze the impact of terrorism in Pakistan on the inflows of foreign direct investment (FDI), portfolio investments, and migrant remittances. We find that FDI decreases substantially as a result of terrorist activity, whereas portfolio investments show little change. In contrast, migrant remittances show a significant increase. These differences are also evident in financial flows from major source regions and top sending countries. The results are robust to the use of alternative definitions and indicators of terrorism as well as the inclusion of various macroeconomic variables. These findings indicate that foreign private capital flees an economy suffering from terrorism whereas migrant remittances are the only financial flows that increase during difficult times.
hdl:10398/9291
Keywords: 330; Terrorism; 9/11; FDI; Portfolio investment; Remittances; Developing countries; Pakistan; Terrorismus; Auslandsinvestition; Portfolio-Investition; Rücküberweisungen; Pakistan